A Case of Prune Belly Syndrome with Uro-rectal Malformation Sequence - Sushma Nayar; Femela Muniraj; Prabha Swaminathan (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Prune belly syndrome (PBS) is a congenital and rare condition which presents apartialor complete triadofde𿿿cienciesorabsence of musclesof abdomen, abnormalities in the genital organs like cryptorchidism and abnormalities of the urinary tract. This condition is usually not compatible with life. Case presentation: A 26-year-old female, fourth gravida with 1 alive and well child and 2 abortions, a known case of hypothyroidism, delivered a stillborn baby at 19 weeks of gestation. On autopsy there was lax, “prune belly” like abdominal wall, low set ears with club foot, hypoplastic lungs, crytorchidism, blind cloacal sac, urachal sac, hypoplastic left kidney, hydroureter, urethral and anal atresia. A case of prune belly syndrome with urorectal malformation sequence was diagnosed. Conclusion: Anomaly scan should be advised wherever a routine obstetric scan shows abnormality of the lungs or urinary system to rule out prune belly syndrome